Attitudes, habits and barriers in the consumption of plastic-packaged beverages in Medellin: a multivariate analysis - Muñetón-Santa, Guberney; Valencia-Cárdenas, Marisol; Vanegas-López, Juan Gabriel; Restrepo-Morales, Jorge Aníbal (Sociedad y Economía, 2019)
The habits or behaviors of consumption regarding the environmental problem caused by consumption are not always consistent with environmentalist attitudes. In this paper, the causal relationship between the at- titudes, barriers and habits of consumers of PET products in the city of Medellin is estimated. The analysis was conducted using Poisson regression models and Structural Equation Modeling based on the information captured from a sample of 300 consumers. The findings indicate a lack of environmental awareness, since the consumption of PET products increases in people who claim that contamination does not affect their personal life. On the other hand, for those who are concerned about pollution, the choice of products is influenced by differences in the price. In addition to this, a lack of knowledge regarding which is the friendliest packaging to the environment was also evidenced.